2022
DOI: 10.7498/aps.71.20220636
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal growth and development promoted by low-intensity roadband terahertz radiation

Abstract: Terahertz waves are located in the energy level range of hydrogen bonding and van der Waals forces, and can directly couple with proteins to excite the nonlinear resonance effect of proteins. Therefore, terahertz can affect the conformation of proteins, the structure and function of neurons. Primary cerebral cortex neurons of SD rats were cultured in vitro. Neurons were radiated 3 days by THz with frequency of 0.3-3THz and a power of 100μW; record the growth and development indicators of neurons (Cell body are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition, there was a strong correlation between the effect of terahertz radiation on neuronal growth and the developmental cycle in which the neuron was located. However, the terahertz waves’ effect on neuronal growth and development was not significant when neurons were in a slow developmental state [ 38 ]. It has been shown that in vitro cultured neurons grow slowly at 6–24 h after inoculation, and during the latency period neurons undergo apposition and adaptation to their environment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, there was a strong correlation between the effect of terahertz radiation on neuronal growth and the developmental cycle in which the neuron was located. However, the terahertz waves’ effect on neuronal growth and development was not significant when neurons were in a slow developmental state [ 38 ]. It has been shown that in vitro cultured neurons grow slowly at 6–24 h after inoculation, and during the latency period neurons undergo apposition and adaptation to their environment.…”
Section: Discussionmentioning
confidence: 99%
“…No existing studies have clarified the mechanism by which terahertz waves regulate dynamic neuronal growth, but some studies have reported that terahertz radiation can alter gene expression associated with neuronal growth at the molecular level [ 23 ]. Other studies have reported that terahertz radiation can alter the proportional size of AMPA (α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid) receptor isoforms at the protein level [ 38 ], thus affecting the permeability of AMPA receptor channels to Ca 2+ [ 49 ]. Neuronal growth is correlated with intracellular Ca 2+ concentration, where higher or lower concentrations prevent neuronal protrusions from growing while appropriate Ca 2+ concentrations promote continuous protrusion growth [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations